Proceedings of the 7th Asia Dengue Summit, June 2024 - Zulkifli Ismail; Duane J. Gubler; Tikki Pangestu; Usa Thisyakorn; Nattachai Srisawat; Daniel Goh; Maria Rosario Capeding; Lulu Bravo; Sutee Yoksan; Terapong Tantawichien; Sri Rezeki Hadinegoro; Kamran Rafiq; et al. (Vaccines)
Background: The 7th Asia Dengue Summit (ADS), titled “Road Map to Zero Dengue Death”, was held in Malaysia from 5 to 7 June 2024. The summit was co-organized by Asia Dengue Voice and Action (ADVA); Global Dengue and Aedes-Transmitted Diseases Consortium (GDAC); Southeast Asian Ministers of Education Tropical Medicine and Public Health Network (SEAMEO TROPMED); Fondation Mérieux (FMx); and the International Society for Neglected Tropical Diseases (ISNTD). Objectives: Dengue experts from academia and research, as well as representatives from the Ministries of Health, Regional and Global World Health Organization (WHO), and International Vaccine Institute (IVI), came together to highlight the crucial need for an integrated approach for dengue control and achieve the target of zero dengue deaths. Methods: With more than 50 speakers and delegates from over 28 countries, twelve symposiums, and three full days, the 7th ADS highlighted approaches to curb the growing danger of dengue. The summit included topics ranging from emerging dengue trends, insights from dengue human infection models, the immunology of dengue, and vaccine updates to antivirals and host-directed therapeutics. Conclusions: The 7th Asia Dengue Summit reinforced the importance of an integrated, collaborative approach to dengue prevention and control. By bringing together diverse stakeholders and launching innovative initiatives such as the Dengue Slayers Challenge, the summit advanced the regional and global agenda to achieve zero dengue deaths. The exchange of knowledge and strategies at the summit is expected to contribute significantly to improved dengue management and community engagement in affected regions.